INTERRELATION BETWEEN THE COURT AND THE PRIVATE MEDIATION, THE NEED TO DIFFERENTIATE THE COURT MEDIATION FORMS IN GEORGIA AND THE AUTHORITY OF THE JUDGE DURING ADMINISTRATION OF THE EACH SINGLE FORM (Law and world, 2019)
It is doubtful that in the conditions of mediation institutionalization, its successful functioning, with other means of dispute settlement, is not only the subject of private interest during individual proceedings. It is also the fact of public importance. However, in the Georgian reality, mediation is considered as a new institution. Most material, procedural or ethical issues related to it have not been regulated at the legislative level, including, the connection between mandatory/judicial and voluntary mediation. Meanwhile, the growing demands of the legal profession require compliance of internal legislation with modern development trends. Considering this fact, the work concentrates on the inter-relationship of mandatory/judicial and voluntary mediation. The signs of mandatory/ judicial and voluntary mediation are discussed. Analysis of court mediation practice and the existing regulatory legislation has been carried out. Recommendations for improvement of legislation have been developed. Each suggested regulation will help in the process of perfection of legislation and the development of the institute.